Conciliating States and Locations: Towards a More Comprehensive and In- Depth Account of the Spanish Copula Estar - Mangialavori Rasia, Maria Eugenia (2013)
The case of estar may reveal how different proposals of study have failed to grasp grammatically relevant semantic features shared by its occurrences. The results of this study indicate that an integrative analysis of estar clauses would account not only for the consistent lexical properties observed - comprising (a)analogous lexical-syntactic structure predicting possible copular complements, (b)analogous selectional restrictions and (c)interpretative effects -, but also for the complementary distribution of two aspectually nontrivial verbal alternations (ser / estar and estar / haber). Our proposal lays on the standard syntactic structure of copular clauses - assumed to embrace locative clauses, against what traditional Spanish grammar suggests - in combination with (i) the structural analogy between estar’s alternative complements (APs and PPs) and (ii) the understanding of states as abstract spatial domains (be at). Thus, the eventual differences between clauses like ‘estoy triste’ and ‘estoy en casa’ could be accounted for by virtue of the semantic / syntactic properties of the lexical head selected.